2009
DOI: 10.1038/nature08026
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a cytolytic α-helical toxin pore reveals its assembly mechanism

Abstract: Pore-forming toxins (PFTs) are a class of potent virulence factors that convert from a soluble form to a membrane-integrated pore. They exhibit their toxic effect either by destruction of the membrane permeability barrier or by delivery of toxic components through the pores. Among the group of bacterial PFTs are some of the most dangerous toxins, such as diphtheria and anthrax toxin. Examples of eukaryotic PFTs are perforin and the membrane-attack complex, proteins of the immune system. PFTs can be subdivided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
509
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(526 citation statements)
references
References 44 publications
16
509
0
1
Order By: Relevance
“…Other studies with the bacterial pneumolysin toxin have shown that there is indeed a conformational transition from the membrane-bound prepore to the transmembrane functional pore by the substantial refolding of -helical regions into membrane-insertedhairpins (Tilley Cell 2005) [56]. Very recently, the structural transformations of -sheets and loop regions to -helices have also been observed during pore formation of the Escherichia coli cytotoxin (ClyA) (Mueller Nature 2009) [57]. This may conceivably reflect that -helix 7 in the Cry4Ba pore-forming domain might be able to refold into an extended -hairpin to insert into the lipid membrane, though the hairpin contains several charged and polar-uncharged residues that are energetically unfavourable for membrane insertion.…”
Section: Insights Into the Mechanism Of Membrane Pore Formationmentioning
confidence: 98%
“…Other studies with the bacterial pneumolysin toxin have shown that there is indeed a conformational transition from the membrane-bound prepore to the transmembrane functional pore by the substantial refolding of -helical regions into membrane-insertedhairpins (Tilley Cell 2005) [56]. Very recently, the structural transformations of -sheets and loop regions to -helices have also been observed during pore formation of the Escherichia coli cytotoxin (ClyA) (Mueller Nature 2009) [57]. This may conceivably reflect that -helix 7 in the Cry4Ba pore-forming domain might be able to refold into an extended -hairpin to insert into the lipid membrane, though the hairpin contains several charged and polar-uncharged residues that are energetically unfavourable for membrane insertion.…”
Section: Insights Into the Mechanism Of Membrane Pore Formationmentioning
confidence: 98%
“…include ShET1 (characterized as an AB 5 toxin in Shigella flexneri) 62 and HlyE (a pore-forming toxin) 63 have also been proposed to contribute to EAEC virulence.…”
Section: Molecular Mechanisms Of Virulencementioning
confidence: 99%
“…It was proposed that the observed structure is the prepore of actinoporins. Prepores were observed in many ␤-PFT (4) and were proposed also for some ␣-PFT (5,29).…”
mentioning
confidence: 99%
“…In general, the details of the pore-forming mechanism of ␣-PFT are not as well understood as those of the ␤-PFT. Apart from structural details of the pore formed by cytolysin A from Escherichia coli (5), molecular properties of ␣-PFT pores are poorly known (i.e. the stoichiometry of the pore, protein regions that participate in the final pore, etc.)…”
mentioning
confidence: 99%